2012
DOI: 10.1042/bj20121259
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-binding proteins of Artemia diapause cysts participate in formation of the embryonic cuticle layer of cyst shells

Abstract: The brine shrimp Artemia reproduces either ovoviviparously, producing free-swimming nauplii, or oviparously, producing encysted embryos (diapause cysts) able to cope with harsh and complex habitats. When the cysts enter diapause they are encased in a complex external shell that protects them from certain extreme environments. The genomic comparison of oviparous and ovoviviparous ovisacs has been described previously. We isolated three significantly up-regulated genes in oviparous oocytes and identified them as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Ovoviviparously developing embryos of Artemia franciscana Kellogg 1906 emerge from females as swimming nauplii, whereas oviparous development yields gastrulae encased in chitinous shells, termed cysts (Jackson and Clegg, 1996;Liang and MacRae, 1999;MacRae, 2003;Ma et al, 2013) (Fig. 1).…”
Section: *Author For Correspondence (Tmacrae@dalca)mentioning
confidence: 99%
“…Ovoviviparously developing embryos of Artemia franciscana Kellogg 1906 emerge from females as swimming nauplii, whereas oviparous development yields gastrulae encased in chitinous shells, termed cysts (Jackson and Clegg, 1996;Liang and MacRae, 1999;MacRae, 2003;Ma et al, 2013) (Fig. 1).…”
Section: *Author For Correspondence (Tmacrae@dalca)mentioning
confidence: 99%
“…Three chitin binding proteins (CBPs) from Artemia parthenogenetica (a shrimp) have been found involved in oviparous development. Moreover, it was found that these proteins are involved in the embryonic cuticular layer and all three CBPs have shown carbohydrate-binding activities [15]. Nonetheless, chitin binding proteins have been found involved in adhesion strategy of some pathogenic bacteria, including E. coli, Listeria monocytogenes and Vibrio cholerae during the intestinal inflammation in humans [16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some chitin binding proteins have shown synergistic action with chitinases either specifically or non-specifically [4]. They are believed to have important roles such as antifungal activity, oviparous and cuticular layer development, biosynthesis of fungal cell walls and anti-inflammatory actions [5, 6]. Moreover, they have been found involved in adhesion strategy of some pathogenic bacteria [7].…”
Section: Introductionmentioning
confidence: 99%